Highly robust nanostructured carbon films by thermal reconfiguration of ionomer binding. Issue 46 (17th November 2020) - Pyo, Jae-Bum; Kim, Ji Hun; Kim, Taek-Soo
Abstract : A dramatic improvement in the mechanical robustness of fragile carbon nanoparticle films formed by a network of ionomer binders. Abstract : The fragile nature of the ionomer-bound carbon film electrode is a primary obstacle to achieving long-term durability of advanced devices, such as fuel cells, electro-active polymer actuators, and supercapacitors, because of its direct correlation with the disconnection of charge transporting paths and the increment in contact resistance. Here, a dramatic improvement in the electrode's robustness is demonstrated, which overcomes its conventionally known brittleness. Through thermal reconfiguration of the ionomer binding, the mechanical properties of the electrode, specifically the Young's modulus, tensile strength, and elongation, are improved by approximately 4-fold, 20-fold, and 28-fold, respectively, compared with the previously reported intrinsic properties. The ionomer's melt flow allowed over the transition temperatures promotes nanostructural interconnections among the neighboring carbon agglomerates by self-alteration of the ionomer binding and filling of small voids. This structural reconfiguration primarily contributes to relieve the load concentration by enhancing the continuity of the load carrying ionomer in the nanostructure. The potential of these highly robust electrodes to resolve mechanical failures in devices is investigated under hygrothermal buckling and cyclic bending loads, demonstrating sufficient endurance without cracking, delamination, and significant performance degradation.